THE IMPLEMENTATION OF THE ENGLISH CURRICULUM IN PUBLIC SCHOOLS IN BANGLADESH: BETWEEN THEORY AND PRACTICE - Airich Angel Mahinay; Prashant S . Mothe (CV. Fahr Publishing, 2025)
This study investigates the implementation of the English curriculum in public secondary schools in Bangladesh, with a specific focus on the gap between policy and classroom practice. The primary objective is to explore how contextual factors—such as teacher preparedness, material availability, classroom conditions, and sociolinguistic diversity—influence the successful enactment of communicative language teaching (CLT) as outlined in the national curriculum. Employing a literature-based research method, this study systematically reviews empirical studies published in the last five years, using thematic content analysis and meta-synthesis to identify key implementation challenges and patterns. The findings reveal that curriculum goals often fail to translate into practice due to systemic barriers, particularly in rural and under-resourced regions, where teachers lack adequate training, materials are outdated or irrelevant, and classroom environments are not conducive to communicative engagement. A notable contribution of this research lies in its novelty: it introduces a comparative perspective between urban and rural school contexts, adopts a longitudinal framework to assess sustainability over time, and explicitly links implementation practices with student communicative outcomes—an area previously underexplored. These insights provide a more nuanced, context-sensitive understanding of the English curriculum landscape in Bangladesh. The study concludes that meaningful reform must go beyond curriculum design and address systemic inequalities, teacher development, and localized support mechanisms. The implications of this research extend beyond the Bangladeshi context, offering applicable insights for similar EFL education systems in the Global South striving to implement communicative curriculum reform in resource-constrained settings.